Primary care cohort study in the sequence of diagnosing chronic respiratory diseases and prescribing inhaled corticosteroids. (December 2018) - Geraets, Ilja; Schermer, Tjard; Kocks, Janwillem; Akkermans, Reinier; Bischoff, Erik; Bemt, Lisette
Abstract To prevent unnecessary use of inhaled corticosteroids (ICS), ICS treatment should only be started when the diagnostic process of asthma and COPD is completed. Little is known about the chronological order between these diagnoses and the start of ICS. We performed a retrospective cohort study, based on electronic medical records of 178 Dutch general practices, to explore the temporal relations between starting continuous use of ICS and receiving a diagnosis of asthma and/or COPD. The database included information of patients who were registered with a diagnosis of asthma and/or COPD in one of the practices during January 1, 2012 and December 31, 2013. Two or more successive prescriptions of ICS within 6 months were considered as continuous ICS treatment. The chronological order of events based on available dates were analysed using descriptive analyses. For 8507 patients with asthma, 4024 patients with COPD, and 801 patients with asthma–COPD overlap (ACO), the order of events could be analysed. In total, 1857 (14.4%) patients started ICS prior to their diagnosis, 11.5, 20.8, and 10.0% of patients with asthma, COPD, and ACO, respectively. In 53.4% of the patients, the first prescription of ICS was a combination inhaler with a long-acting bronchodilator. In this real-life primary care cohort, one in seven patients started ICS treatment prior to their diagnosis and approximately half of the patients started with a combination inhaler. Our findings suggest that there is relevant room for improvement in the pharmaceutical management of patients with these chronic respiratory diseases.